The impact of interventional neuroradiology on neurosurgical training. - Vindlacheruvu, R. R. (2003)
Aneurysmal subarachnoid haemorrhage carries a high mortality and morbidity. Surgical treatment (craniotomy and clipping of the aneurysm) has been, until recently, the gold standard treatment. Endovascular embolisation treatment has rapidly evolved and the evidence available suggests that the results are as good as surgery. Endovascular treatment successfully occludes the aneurysm to prevent re-haemorrhage, whilst reducing the procedural morbidity when compared to craniotomy and clipping. It is perceived to be of particular benefit for aneurysms in the posterior cerebral circulation where operative morbidity and mortality are significantly higher than for aneurysms on the anterior circle of Willis. The establishment of endovascular treatment has reduced the number of cases being treated surgically, and this has had a significant effect on surgical training. We analysed the management of all ruptured aneurysms treated in our unit over a 4-year period. During the same period, an endovascular service was established in the unit. We devised a novel system for the angiographic grading of aneurysms in order to evaluate the impact that coiling has had on surgical training. The results show that as few as four aneurysms per year would be appropriate for specialist registrars to operate upon. We propose some mechanisms for maintaining high quality surgical training.